Utilitarian Aspects of Postmortem Computed Tomography. Issue 4 (December 2015) - Matshes, Evan W.; Snyder, Vivian S.; Andrews, Sam W.
Computed tomography has been used in clinical medicine for decades, but only recently introduced into the forensic pathology setting. The reasons for the slow adoption of this technology into the autopsy suite are various, including concerns about funding, infrastructural maintenance, training, competency, and scope of utilization. Practical experience in a busy statewide medical examiner department confirmed the utility of this technology as a part of daily practice. The impact of postmortem computed tomography (PMCT) on casework can be stratified into three broad groups: where PMCT 1) supplants invasive autopsy, 2) supplements invasive autopsy, or 3) has limited or no potential for impact on practice. A detailed understanding of the practical uses of this science is important for the practicing forensic pathologist so as to guide decisions about the ways in which PMCT can be implemented within their own institutions and utilized on a daily basis. Dramatic changes in personal and institutional practice trends can be observed once forensic pathologists are comfortable with the evaluation, documentation, and interpretation of PMCT data. Examples of potential paradigm shifts include the performance of only external examination and PMCT instead of invasive autopsy in many cases of motor vehicle fatalities, suicide with violence, and broad categories of death due to natural disease. Over time, the authors believe that the PMCT will become one of the fundamental tools in the forensic pathologist's toolkit.